Passion for an activity and quality of interpersonal relationships the mediating role of emotions. [article]. - Philippe, Frederick L.
Our purpose in this research was to investigate the role of passion (Vallerand et al., 2003) for a given activity in the quality of interpersonal relationships experienced within the context of that activity nin 4 studies. Study 1 demonstrated that a harmonious passion was positively associated with the quality interpersonal relationships within the context of the passionate activity, whereas an obsessive passion was unrelated to it. Furthermore, in line with the broaden-and-build theory (Fredrickson, 2001), results also showed that positive emotions experienced at work fully mediated the relation between harmonious passion and quality of interpersonal relationships. Obsessive passion was not associated with positive emotions. Study 2 replicated the results from Study 1 while controlling for trait extraversion. Also, in Study 2, we examined the negative mediating negative role emotions between obsessive passion and quality on interpersonal relationships. Finally, Studies 3 and 4 replicated the results of Study 2 with prospective designs and with objective ratings of interpersonal relationships quality. Implications for the dualistic model of passion and the broaden-and-build theory are discussed.
Keywords: Passion; Interpersonal relationships; Emotion; Broaden-and-build theory